Inflammatory Marker Profile of Sepsis Patients at Royal Prima General Hospital - Lenny; Primta Bangun; Alvin Abrar Harahap (Postgraduate, University of Mataram, 2025)
Sepsis is a serious complication that remains a leading cause of death worldwide, especially among young children and the elderly. Delayed diagnosis remains a major challenge, highlighting the need to develop accurate diagnostic modalities, including inflammatory markers derived from routine blood counts. This study aimed to describe the profile of inflammatory markers in sepsis patients at Rumah Sakit Umum Royal Prima Medan in 2024. This observational study employed a cross-sectional design, analyzing 81 medical records of sepsis patients from Royal Prima General Hospital in 2024, selected using simple random sampling. The variables measured included socio-demographic characteristics (age and sex), leukocyte profile (total leukocyte count, eosinophils, basophils, neutrophils, lymphocytes, and monocytes), and inflammatory indices (NLR, PLR, PNR, LMR, and NLPR). Most sepsis patients were male (50.6%) in the early elderly age group (33.3%), with median leukocyte counts of 17,350 cells/µL, neutrophils at 14,660 cells/µL, and lymphocytes at 1,279 cells/µL. The inflammatory marker indices showed trends of NLR 13.21, PLR 290.74, LMR 1.30, PNR 21.50, and NLPR 0.004. These results support the potential of routine blood inflammatory markers as indicators for sepsis progression.